The COVID-19 pandemic and its impact on mental health. Causes and consequences - an overview - Cioch, Michał Jakub; Kaczmarska, Urszula; Woźniak, Aleksandra; Nowak, Julia; Hermanowicz, Kamil; Doman, Katarzyna; Najdek, Agnieszka; Oleksy, Daria; Mycyk, Marcin; Komada, Dawid (Journal of Education, Health and Sport, 2025)
Introduction: This article provides an overview of the COVID-19 pandemic, which lasted from 2019 to 2023, and its impact on mental health. It will discuss risk factors leading to mental health disorders during the pandemic. Attention will also be given to the risk factors and possible causes, groups most affected and the ways to deal with mental disorders during a pandemic will also be discussed. Aim of study: The aim of the study is to assess the impact of the COVID-19 pandemic on mental health, identify risk factors and possible causes of mental disorders during this period, and identify groups that are particularly vulnerable to the negative psychological effects of the pandemic. Materials and methods: A comprehensive literature review was conducted using the PubMed database, focusing on articles published up to the end of 2024. The search included the keywords “COVID-19”, “mental health”, “pandemic”, “depression” in different combinations. Relevant studies were selected based on criteria such as causes and risk factors. Special attention was paid to vulnerable groups (e.g., children and the elderly, etc.) and how changes in the pandemic (e.g., social isolation) affected mental health. Conclusion: The pandemic of COVID-19 has affected not only people’s physical health but also their mental health. Studies indicate that during the COVID-19 pandemic, the incidence of mental illnesses increased, and the symptoms of people with mental disorders were exacerbated including symptoms of general anxiety, sleep disorders, depressive disorders, etc. The study discussed risk factors such as social isolation, etc. and how they caused an increase in mental disorders